Peran Mediasi Pembelajaran Organisasi pada Hubungan Budaya Organisasi dan Kinerja - Conchita Valentina Latupapua; Restia Christianty; Wylda Olivia Kowey (Univiversitas Dr. Djar Wattiheluw, 2023)
This study investigates the relationship between the components of organizational culture and Lecturer Performance between academics. It is hypothesized that Organizational Learning has a positive mediating role to explain the relationship between organizational culture and lecturer performance. To reveal the relationship between the components of organizational cultureperception and lecturer performance, a correlational research design was carried out using SMART PLS 3.2 with a total sample of 35 lecturers Organizational Learning plays a role in mediating the relationship between Organizational Culture and Lecturer Performance. The study is limited to one private college, the sample size is not represented, so the limited results have not been able to be used as an extensive reference for private universities. Although there have been studies that discuss the relationship between organizational culture and lecturer performance, not many researchers have researched related to learning as mediation. The results of this paper focus on various aspects of organizational learning for the development of private universities and contribute to the needs of human resource development.